2017
DOI: 10.1111/jbg.12276
|View full text |Cite
|
Sign up to set email alerts
|

Selection of core animals in the Algorithm for Proven and Young using a simulation model

Abstract: SummaryThe Algorithm for Proven and Young (APY) enables the implementation of single-step genomic BLUP (ssGBLUP) in large, genotyped populations by separating genotyped animals into core and non-core subsets and creating a computationally efficient inverse for the genomic relationship matrix (G). As APY became the choice for large-scale genomic evaluations in BLUP-based methods, a common question is how to choose the animals in the core subset. We compared several core definitions to answer this question. Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Regression coefficients (b1) of adjusted phenotypes on genomic EBV, for different groups of validation animals (purebred animals L1 and L2, and their crosses C) with a different source of phenotypes available, shown for traits 1 (T1) and 2 (T2), under the first model (M1; 2-trait animal model without the distinction between the lines) and second model (M2; when that trait was separated into 3 traits based on the line of the animals) populations in different species (e.g., Pocrnic et al, 2016b); however, the application of this concept for crossbred/multibreed contexts was unclear. Bradford et al (2017) found, by simulating a purebred population, that any core definition is robust in populations with complete pedigree; otherwise, selecting core animals randomly across multiple generations gives desirable accuracies. This is attributed to a random sample that increases the likelihood of all generations of genotyped animals being represented in the core group.…”
Section: Resultsmentioning
confidence: 99%
“…Regression coefficients (b1) of adjusted phenotypes on genomic EBV, for different groups of validation animals (purebred animals L1 and L2, and their crosses C) with a different source of phenotypes available, shown for traits 1 (T1) and 2 (T2), under the first model (M1; 2-trait animal model without the distinction between the lines) and second model (M2; when that trait was separated into 3 traits based on the line of the animals) populations in different species (e.g., Pocrnic et al, 2016b); however, the application of this concept for crossbred/multibreed contexts was unclear. Bradford et al (2017) found, by simulating a purebred population, that any core definition is robust in populations with complete pedigree; otherwise, selecting core animals randomly across multiple generations gives desirable accuracies. This is attributed to a random sample that increases the likelihood of all generations of genotyped animals being represented in the core group.…”
Section: Resultsmentioning
confidence: 99%
“…This was successfully demonstrated for several purebred populations in different species (e.g., Pocrnic et al, 2016b); however, the application of this concept for crossbred/multibreed contexts was unclear. Bradford et al (2017) found, by simulating a purebred population, that any core definition is robust in populations with complete pedigree; otherwise, selecting core animals randomly across multiple generations gives desirable accuracies. This is attributed to a random sample that increases the likelihood of all generations of genotyped animals being represented in the core group.…”
Section: Resultsmentioning
confidence: 99%
“…To form G APY −1 , we randomly chose a core group of genotyped animals. A randomly selected set of core animals has worked well in earlier analyses (Fragomeni et al, 2015;Bradford et al, 2017). Pocrnic et al (2016) found that the choice of core animals did not affect the accuracy of genomic evaluation as long as their number was equivalent to or larger than the number of largest eigenvalues that explained 98% of variation in G. In this study, we set the number of core animals to 18,359, which was determined with the eigenvalues calculated as the squared singular values of the centered marker matrix (say, Z) that includes all genotyped animals formed as formed by VanRaden (2008).…”
Section: Single-mentioning
confidence: 99%